Design and Development of Manual Equipment Hooking Machine for Industrial Operations - Milkessa Gurmesa Gebisa (Techniques and Innovation in Engineering Research Vol. 6, 2022)
During material handling, different problems arise on our body and the material handling may not be completed on time at a possible minimum energy consumption which in turn leads to customer dissatisfaction and loss of profit. Having this in a mind, this paper is conducted to solve such problems. That means the objective of the paper is to design and developing the lifting machine, to simplify lifting heavy load, to increase the productivity by minimizing operation time and to increase safety of the operation. To achieve this objective, the necessary information is collected through primary and secondary data sources, the collected data is analyzed and presented using table, graphically, and some, literatures and etc. Finally, we are interested to recommend about our design targeted to: To increase the efficiency of the product at minimum cost using the hooking machine gives many services for manufacturing company and reduce the accidents on human body. Designing of this manual hooking machine that can be operate mechanically by spur gears mechanism to avoid hazards of workers and to increase productivity, to achieve its target and satisfy its employers.